Analysis Of The Influence Of Foreign Capital Investment, Exports, Imports And Foreign Debt On Foreign Exchange Reserves Of Asean Countries - Abdul Rasyid; Eva Yuniarti Utami; Jamaluddin Majid; Prety Diawati; Erasma (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Because a country lacks the resources necessary to meet its own demands due to a lack of resources, international trade is today essential to a country's development. This fact cannot be disputed. To gain what is required to quicken the country's development operations, support or cooperation with other nations that have benefits or superior resources is therefore required. This study examines how foreign debt, imports, exports, and foreign direct investment (FDI) affect foreign exchange reserves. The Random Effect Model (REM) was used in this study's panel data analysis with research samples from ASEAN's emerging nations, including the Philippines, Indonesia, Cambodia, Laos, Malaysia, Myanmar, Thailand, and Vietnam, from 2017 to 2022. The study's findings indicate that while imports have a negative and major impact on the economy, exports and foreign debt have a partially positive and large impact. FDI, nevertheless, has a negligible and unimportant impact. Foreign debt, FDI, imports, and exports all have an impact on foreign exchange reserves simultaneously.